Pengaruh Karakteristik, Pengetahuan Dan Sikap Petugas Pemegang Program Tuberkulosis Paru Puskesmas Terhadap Penemuan Suspek TB Paru Di Kabupaten Blora - Widjanarko, Bagoes; Prabamurti, Priyadi Nugraha; Widayat, Edi (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : The discovery of clients with lung tuberculsosis suspect at Blora Regency within the year of 2002 were 9.8%, year of 2003 were 27.3% and year of 2004 were 23.3%. Moreover, until March 2005 the discovery of lung tuberculsosis suspects were 876 cases (8,64%). This number not yet reached 40% of Blora Regency target. Knowledge andattitude of health workers who held lung tuberculosis program was closely related with case detection of lung tuberculosis. The aims of this study were to search the description of knowledge, attitude, and characteristics of health workers who held lung tuberculosis program at community health centres and the influence of case detection of lung tuberculosis suspects at Blora Regency.Method : This study is an explanatory research and uses cross sectional approach. The subjects consisted of a total population of 52 health workers who held lung tuberculosis program at community health centres. Data were collected using questionnaires and were analysed using logistic regression statistical method.Result : The study revealed that there were a strong correlation between characteristics (p=0.001), training of health workers (p=0.01), knowledge of health workers (p=0.01) attitude (p=0.01) and supervision of vice supervisor (p=0.01). Multivariate analises showed that the most valuable correlation discovered were between training of health workers (p=0.002) and knowledge of health workers (p=0.021) in the of case detection oflung tuberculosis suspects.Key Words : suspect, health workrs who held program, lung tuberculosis, knowledge, attitude.